The EU Response to US Trade Tariffs - Maria Demertzis; Gustav Fredriksson (Intereconomics, 2018)
The greatest challenge for the EU in trying to identify an optimal response is understanding the motives behind the US strategy. The rhetoric, and more recently also actions, of the current US administration on trade and the global multilateral system are a real threat to the process of globalisation. While the costs are not immediate, they will materialise and they will be hard to revert.
Keywords: 330; European governance; Trade disputes; Trade policy; Trade restrictions; USA; WTO; Game theory